Speech and Institutional Choice - Thomas B. Nachbar (Washington University Journal of Law & Policy, 2006)
Even if an authoritarian state cannot successfully control all of the conduits by which information crosses its borders, successfully targeting a few of the largest ones is likely to bring enough of a return to justify the effort, a point at the heart of John Palfrey and Robert Rogoyski’s Essay for this conference. What is true of states and regulation for political gain will be true of private interests and regulation for financial gain. Control over the means of creating and sharing the digital content would provide any firm substantial rents, either in the form of higher prices or by favoring its own content or associated technologies. The pervasive presence of network effects—both actual and virtual—in digital technology markets suggests that such private actors are likely to enjoy considerable regulatory control over particular technologies once dominated, and there is every reason to believe that such control, once vested, will be employed to the benefit of those who hold control and to the detriment (or, at the very best, indifference) of those who do not. The likely result is both wealth transfer to those who control particular digital technologies and, as a consequence of their vested interest in maintaining that control, the retardation of future technological development.
Keywords: Digital technology; Freedom of speech; Obscenity (Law); Censorship; Information technology; Internet; United States Constitution; United States